Recurrent Oncocytoma of the Lacrimal Sac. (28th February 2022) - Almutairi, Faris; Alsamnan, Mazen; Maktabi, Azza; Elkhamary, Sahar; Alkatan, Hind M.; AlOtaibi, Humoud
Abstract : Oncocytoma of the lacrimal sac is an extremely rare tumor. In this report, we present the case of an 82-year-old woman who presented with swelling in the region of the lacrimal sac. Systemic examination and ophthalmic examination of both eyes were unremarkable. Computed tomography of the brain and orbits revealed a mass lesion involving the right lacrimal sac with expansion of the related nasolacrimal duct. Neither bone destruction nor tissue invasion was observed. Right external dacryocystectomy and debulking of the tumor were performed. Histopathological examination of the surgical specimen showed oncocytic cells arranged in an adenomatous fashion, and a diagnosis of benign oncocytoma was made. Three years later, the same patient presented with a similar complaint that was pathologically proven to be a recurrent benign oncocytoma of the lacrimal sac.